Good faith in the abbreviated selection processes - minor amount, in the Administrative and Accounting Center of the National Army Personnel (2020)
In Colombia, a continuous report has been presented on behalf of different governmental and non-governmental entities, which consists of the fact that the Colombian National Army has presented observations on matters of state contracting which refer to the transgression of the principles and related pre-existing laws. with the principle of good faith within the different contractual processes, executed under the different modalities, in the acquisition of Goods and Services, leaving as a result the non-participation in the different offers made, thereby allowing an unnecessary gap to be generated between these important sectors of the economy